2019
DOI: 10.1002/lom3.10303
|View full text |Cite
|
Sign up to set email alerts
|

Application of the isotope pairing technique in sediments: Use, challenges, and new directions

Abstract: Determining accurate rates of benthic nitrogen (N) removal and retention pathways from diverse environments is critical to our understanding of process distribution and constructing reliable N budgets and models. The whole‐core 15N isotope pairing technique (IPT) is one of the most widely used methods to determine rates of benthic nitrate‐reducing processes and has provided valuable information on processes and factors controlling N removal and retention in aquatic systems. While the whole core IPT has been em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 244 publications
(443 reference statements)
0
27
0
Order By: Relevance
“…Anaerobic NH 4 + oxidation (anammox) rates have previously been shown to be negligible at the collection site (data not shown). The approach is thoroughly reviewed by Robertson et al (2019).…”
Section: Sediment Denitrification Measurementsmentioning
confidence: 99%
“…Anaerobic NH 4 + oxidation (anammox) rates have previously been shown to be negligible at the collection site (data not shown). The approach is thoroughly reviewed by Robertson et al (2019).…”
Section: Sediment Denitrification Measurementsmentioning
confidence: 99%
“…Wenk et al (2014) reported a maximum DNRA contribution to NO 3 − reduction of ∼12%, but also suggested that these measurements should be considered conservative, because they neither accounted for the production of 14 NH 4 + from ambient background NO 3 − nor for product NH 4 + potentially retained in the intact sediment cores. The use of intact sediment cores provides a more accurate representation of in situ N-cycling conditions by maintaining the biogeochemical zonation of the sediment relative to slurry methods (Hansen et al, 2000;Robertson et al, 2019). However, relative potential process rates and their specific regulating factors can better be resolved through controlled manipulation experiments (Robertson et al, 2019), such as those performed here (discussed below).…”
Section: Discussion Denitrification Versus Dnra In Lake Lugano Sedimentsmentioning
confidence: 99%
“…The use of intact sediment cores provides a more accurate representation of in situ N-cycling conditions by maintaining the biogeochemical zonation of the sediment relative to slurry methods (Hansen et al, 2000;Robertson et al, 2019). However, relative potential process rates and their specific regulating factors can better be resolved through controlled manipulation experiments (Robertson et al, 2019), such as those performed here (discussed below).…”
Section: Discussion Denitrification Versus Dnra In Lake Lugano Sedimentsmentioning
confidence: 99%
“…The existence of NO3 − reduction pathways, mainly during S2, is the most plausible explanation according to the isotopic data. However, other major issues for 15 N-IPT studies such as uptake and intracellular storage should not be discarded (Robertson et al, 2019). Significant inputs of NO3 − may also promote blooms of diatoms (frequent in Pétrola Lake), which are physiologically adapted to grow rapidly under nitrate-rich conditions (Bronk et al, 2007).…”
Section: Hydrogeochemical Dynamics During Sediment Incubationsmentioning
confidence: 99%
“…The 15 N-IPT was firstly applied on sediment cores to quantify N2 production derived from denitrification (Nielsen, 1992). Since then, many studies have focused on discriminating the relative contribution of N processes using 15 N-IPT, including DNRA, and recently coupled DNRA-anammox (Risgaard-Petersen et al, 2003;Holtappels et al, 2011;Hsu and Kao, 2013;Robertson et al, 2019). Hence, processes such as anammox have been traditionally underestimated.…”
mentioning
confidence: 99%